1995
DOI: 10.1002/bbpc.199500045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Charge Density and Concentration on the Dynamics of Aqueous Polyelectrolyte Solutions

Abstract: We have investigated the dynamics of protonated poly(2‐vinylpyridine) (Mw = 135000) in aqueous solution by dynamic light scattering over a wide concentration range (0.5 ≤ cpe ≤ 100 g/l). The charge density on the polymer chain (degree of protonation α) was varied from 0.26 to 0.62 by hydrochloric acid. The reduced composition variable Λ = αcmpe/ with cmpe and cs the molar concentrations of the polymer repeat unit and salt, respectively, was constant for a given charge density. We always observed two well separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…However, although the Manning's limiting law has proven very successful in the experimentally accessible dilute ragime, 31 it may underestimate the number of condensed counterions in the semidilute regime as suggested by Kuhn et al 32 On the other hand, as for the chain overlapping in the semidilute regime, researchers often reported that the polyelectolyte chains turn to aggregate to form a multichain cluster in the salt-free aqueous solution as observed by dynamic light scattering experiments. [33][34][35][36][37] We have also investigated the chain aggregation phenomenon of NaPSS in the salt-free aqueous solution by dialysis. 23 According to Stevens and Kremer, 8 when the concentration of polyelectrolyte solution is increased, the monomer-monomer repulsion is more strongly screened by forcing the counterion clouds closer to the monomers.…”
Section: Resultsmentioning
confidence: 99%
“…However, although the Manning's limiting law has proven very successful in the experimentally accessible dilute ragime, 31 it may underestimate the number of condensed counterions in the semidilute regime as suggested by Kuhn et al 32 On the other hand, as for the chain overlapping in the semidilute regime, researchers often reported that the polyelectolyte chains turn to aggregate to form a multichain cluster in the salt-free aqueous solution as observed by dynamic light scattering experiments. [33][34][35][36][37] We have also investigated the chain aggregation phenomenon of NaPSS in the salt-free aqueous solution by dialysis. 23 According to Stevens and Kremer, 8 when the concentration of polyelectrolyte solution is increased, the monomer-monomer repulsion is more strongly screened by forcing the counterion clouds closer to the monomers.…”
Section: Resultsmentioning
confidence: 99%
“…10 There are reports in the literature that the same is true for solutions of weakly charged polyelectrolytes with no added salt (poly(methylacrylic acid) partially neutralized with NaOH and P2VP partially protonated with HCl). 8,9 (c) For Λ g 1 and 0.09 e R e e 0.15 the distribution is trimodal (fast mode, τ f ; "intermediate mode", τ int ; slow 5394 Topp et al Macromolecules, Vol. 29, No.…”
Section: Viscositymentioning
confidence: 98%
“…Odijk has pointed out that the theoretical predication on the solution behavior of polyelectrolytes with added salt was straightforward, whereas no satisfactory theory in the absence of salt was available. The polyelectrolyte solutions with no or low added salt have been often regarded as a heterogeneous solution in which the polyions formed a multichain cluster (or domain). For example, Ise et al observed a single broad peak in the small-angle X-ray scattering of polyelectrolyte dilute solution and suggested the presence of quasi-lattice-like ordering domains. In the dynamic light scattering of polyelectrolyte solutions with no or low added salt, a double-exponential correlation function interpreted as consisting of fast and slow modes was frequently reported. The fast mode was interpreted as a coupled diffusion of polyions and counterions.…”
Section: Introductionmentioning
confidence: 99%
“…The polyelectrolyte solutions with no or low added salt have been often regarded as a heterogeneous solution in which the polyions formed a multichain cluster (or domain). For example, Ise et al observed a single broad peak in the small-angle X-ray scattering of polyelectrolyte dilute solution and suggested the presence of quasi-lattice-like ordering domains. In the dynamic light scattering of polyelectrolyte solutions with no or low added salt, a double-exponential correlation function interpreted as consisting of fast and slow modes was frequently reported. The fast mode was interpreted as a coupled diffusion of polyions and counterions. The slow mode was interpreted as the diffusion of multichain domains and regarded as evidence of the existence of polyions' aggregation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation